Uncorrectable hypoxemia due to large pulmonary arteriovenous malformation in a patient with myocardial infarction: a case report - Kang-Un Choi; Jang-Won Son (Journal of Yeungnam Medical Science)
Persistent hypoxemia following myocardial infarction can be challenging to manage and often requires considering uncommon etiologies such as extracardiac shunts. This case report describes a 78-year-old man with persistent hypoxemia post-myocardial infarction, which was ultimately attributed to a large pulmonary arteriovenous malformation (AVM). The patient presented with cardiogenic shock and underwent successful revascularization. Despite clinical improvement, the hypoxemia persisted, prompting further evaluation. Bedside saline contrast echocardiography and computed tomography confirmed the presence of a large pulmonary AVM, explaining the uncorrectable hypoxemia. This case underscores the importance of considering extracardiac shunts in patients with refractory hypoxemia and illustrates the utility of bedside imaging in such situations.